Ultrahigh room temperature electrocaloric response in lead-free bulk ceramics via tape casting. Issue 23 (9th May 2019) - Du, Hongliang; Chang, Yunfei; Li, Chunwang; Hu, Qingyuan; Pang, Jing; Sun, Yuan; Weyland, Florian; Novak, Nikola; Jin, Li
Abstract : An ultrahigh room temperature adiabatic temperature change (∼1.6 K) was realized in a BaTiO3 -based bulk ceramic prepared by the tape casting technique, which makes a giant step-forward for electrocaloric refrigeration. Abstract : Solid-state cooling technology based on the electrocaloric effect is attracting increasing attention as an important alternative to traditional cooling systems in microelectronic and integrated electronics. Lead-free bulk ceramics are considered as one of the promising candidates for middle and large-scale electrocaloric cooling because of their environment-friendliness and large heat absorption capacity. However, the room temperature adiabatic temperature change (Δ T ) in lead-free bulk ceramics has long been limited by their relatively low dielectric breakdown strength ( E b < 60 kV cm −1 ), hindering their practical applications. In this work, we propose to use the tape casting technique as a practicable strategy to enhance the densification and decrease the porosity of lead-free bulk ceramics for achieving a high E b and a large room temperature Δ T . An ultrahigh room temperature Δ T (1.6 K) was realized in a (Ba0.95 Ca0.05 )(Ti0.94 Sn0.06 )O3 (BCTS) bulk ceramic prepared by the tape casting technique, which is 4 times larger than that of the lead-free bulk ceramics with a similar composition prepared by the conventional ceramic preparing approach. More significantly, unlike the other previously reported results, which only show high Δ T in an extremely narrow temperature range, Δ T of the BCTS bulk ceramic increases from 1.6 K to 2.0 K in the temperature range from 300 K to 345 K, which is comparable with that found in the lead-based bulk counterpart. Most importantly, this work opens up a new avenue to explore lead-free bulk ceramics with a large room temperature Δ T for solid-state refrigeration.